Effect of stimulated platelets in COVID-19 thrombosis: Role of alpha7 nicotinic acetylcholine receptor - Jankauskaite, Lina; Malinauskas, Mantas; Snipaitiene, Ausra (Frontiers in Cardiovascular Medicine, 2022)
Since early 2020, SARS-CoV-2-induced infection resulted in global pandemics with high morbidity, especially in the adult population. COVID-19 is a highly prothrombotic condition associated with subsequent multiorgan failure and lethal outcomes. The exact mechanism of the prothrombotic state is not well understood and might be multifactorial. Nevertheless, platelets are attributed to play a crucial role in COVID-19-associated thrombosis. To date, platelets’ role was defined primarily in thrombosis and homeostasis. Currently, more focus has been set on their part in inflammation and immunity. Moreover, their ability to release various soluble factors under activation as well as internalize and degrade specific pathogens has been highly addressed in viral research. This review article will discuss platelet role in COVID-19-associated thrombosis and their role in the cholinergic anti-inflammatory pathway. Multiple studies confirmed that platelets display a hyperactivated phenotype in COVID-19 patients. Critically ill patients demonstrate increased platelet activation markers such as P-selectin, PF4, or serotonin. In addition, platelets contain acetylcholine and express α7 nicotinic acetylcholine receptors (α7nAchR). Thus, acetylcholine can be released under activation, and α7nAchR can be stimulated in an autocrine manner and support platelet function. α7 receptor is one of the most important mediators of the anti-inflammatory properties as it is associated with humoral and intrinsic immunity and was demonstrated to contribute to better outcomes in COVID-19 patients when under stimulation. Hematopoietic α7nAchR deficiency increases platelet activation and, in experimental studies, α7nAchR stimulation can diminish the pro-inflammatory state and modulate platelet reactiveness via increased levels of NO. NO has been described to inhibit platelet adhesion, activation, and aggregation. In addition, acetylcholine has been demonstrated to decrease platelet aggregation possibly by blocking the e p-38 pathway. SARS-COV-2 proteins have been found to be similar to neurotoxins which can bind to nAChR and prevent the action of acetylcholine. Concluding, the platelet role in COVID-19 thrombotic events could be explained by their active function in the cholinergic anti-inflammatory pathway.